P286 Bariatric surgery in inflammatory bowel disease: outcome and safety from a GETAID registry population. (25th January 2019) - Reenaers, C; Nachury, M; Stefanescu, C; Pineton de Chambrun, G; Laharie, D; Boileve, J; Viennot, S; Peyrin-Biroulet, L; Roblin, X; Grimaud, J-C; Bouguen, G; Nahon, S; et al.
Abstract: Background: Morbid obesity increased in the past 2 decades including in the inflammatory bowel disease (IBD) population with up to 15 to 20% of obese IBD patients in Europe and 20 to 40% in the USA. Bariatric procedures dramatically changed the management of obesity. Few data are available on the feasibility and the safety of these procedures in the IBD population. The aim of this work was to assess the safety and the efficacy of bariatric surgery (BS) in IBD patients and to describe the outcomes of IBD after BS. Methods: IBD patients with a history of BS were recruited in GETAID centres. The demographic and the disease characteristics were retrospectively reviewed. The type of BS, the early post-operative complications and the long-term IBD outcomes were recorded. Results: In total, 57 patients (44 Crohn's disease, 12 ulcerative colitis and 1 unclassified colitis) from 14 GETAID centres underwent a BS after the diagnosis of IBD. At the time of BS the mean age was 39 years (SD ±11), the mean disease duration was 122 months (SD ±77) and 42% were on biologic therapy. The BS was a sleeve gastrectomy in 44/57 (77.2%), an adjustable gastric banding in 10/57 (17.5%) and a gastric bypass in 3/57 (5.3%). Five patients (8.8%) experienced an early post-operative complication including 1 abscess with septic shock, 1 stricture of the sleeve with secondary bypass, 1 bypass converted to sleeve for peroperative technical reasons, 1 abdominal wall infection and 1 banding narrowing. The mean weight and BMI at the time of BS were 120 kg (SD ±19) and 42 kg/m 2 (SD ±5.7), respectively. The mean weight loss at maximal follow-up (median: 37.8 months–SD ±35.6) post-BS was 28.3 kg (SD ±15). Regarding IBD outcomes, 12 (21%) patients required a treatment modification during the follow-up period, 1 was operated for an IBD flare (ileo-caecal resection for active Crohn's disease) and 3 experienced new perianal lesions. Anaemia was more frequent after BS (14.3% vs. 5.3% pre-BS). Conclusions: In the IBD population, BS is feasible and the sleeve gastrectomy has become the most common procedure. Close to 10% of early post-operative complications were observed in our cohort. The course of IBD was stable after the procedure with low rates of IBD complications and treatment escalations.